2006
DOI: 10.1094/mpmi-19-0557
|View full text |Cite
|
Sign up to set email alerts
|

Different Mutations in the Genome-Linked Protein VPg of Potato virus Y Confer Virulence on the pvr23 Resistance in Pepper

Abstract: Five different amino acid substitutions in the VPg of Potato virus Y were shown to be independently responsible for virulence toward pvr2(3) resistance gene of pepper. A consequence of these multiple mutations toward virulence involving single nucleotide substitutions is a particularly high frequency of resistance breaking (37% of inoculated plants from the first inoculation) and suggests a potentially low durability of pvr2(3) resistance. These five mutants were observed with significantly different frequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
174
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(177 citation statements)
references
References 26 publications
3
174
0
Order By: Relevance
“…Gómez, et al (2009) mainly attributed to the absence of susceptibility factors, such as eIF4E, eIF(iso)4E, eIF4G, eIF(iso)4G, e.g. lsp1 (Lellis et al 2002), pvr2 (Ayme et al 2006), nsv (Nieto et al 2006;Truniger et al 2008), cum2-1 (Yoshii et al 1998), cum1-1 (Yoshii et al 1998, sbm1 (Gao et al 2004), rymv-1 (Albar et al 2003;Albar et al 2006), rym4/5 (Stein et al 2005). A number of recessive resistances to other members of the Potyviridae correspond to eIF4E or eIF(iso)4E (Robaglia and Caranta 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Gómez, et al (2009) mainly attributed to the absence of susceptibility factors, such as eIF4E, eIF(iso)4E, eIF4G, eIF(iso)4G, e.g. lsp1 (Lellis et al 2002), pvr2 (Ayme et al 2006), nsv (Nieto et al 2006;Truniger et al 2008), cum2-1 (Yoshii et al 1998), cum1-1 (Yoshii et al 1998, sbm1 (Gao et al 2004), rymv-1 (Albar et al 2003;Albar et al 2006), rym4/5 (Stein et al 2005). A number of recessive resistances to other members of the Potyviridae correspond to eIF4E or eIF(iso)4E (Robaglia and Caranta 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Two sets of PVY variants were used: (i) viral populations derived from the two cDNA clones SON41p and LYE84 and from several of their VPg mutants (14,15) and (ii) representative isolates collected from pepper crops corresponding to different haplotypes according to the VPg sequence. Four mutants of SON41p, named S101G, T115K, T115R, and D119N according to the position and nature of the amino acid substitution in the VPg, were obtained after experimental evolution in HD285 carrying the pvr2 3 resistance allele (14). A fifth mutant, S120C, was excluded because of its lack of stability and difficulty in obtaining a homogeneous inoculum.…”
Section: Methodsmentioning
confidence: 99%
“…The sequences of the VPg-coding regions of 57 PVY isolates collected from pepper crops were determined (references 12, 16, and 17 and the present study), and 12 haplotypes were observed based on the amino acid diversity in the region spanning positions 101 to 123, shown to be critical for pathogenicity toward eIF4E-mediated resistance (14,16). A single isolate was chosen to represent each haplotype for infectivity tests (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Several factors could be responsible for such low resistance durability. The durability of plant resistances to viruses was shown to be linked to: (i) the capacity of the virus to evolve resistance-breaking properties, which is linked to the number of mutations required for such properties (Harrison, 2002;Ayme et al, 2006Ayme et al, , 2007Fabre et al, 2009); and (ii) the impact of these mutations on the virus competitiveness (Jenner et al, 2002;Desbiez et al, 2003;Fabre et al, 2009;Janzac et al, 2010). Concerning TSWV, the trees of the NP and NSs genes (Figs 2 and 3), which correspond to the RNA segment which carries the factor responsible for breakdown of the Tsw resistance, show that multiple acquisitions of the resistance-breakdown properties have affected TSWV history.…”
Section: Insights Into the Low Durability Of The Tsw Resistance In Pementioning
confidence: 99%